1982
DOI: 10.3109/03009748209098110
|View full text |Cite
|
Sign up to set email alerts
|

Myositis Ossificans Circumscripta in Para-/Tetraplegics

Abstract: At the Hospital of Physical Medicine, Hornbaek, we analysed in retrospect 52 cases of myositis ossificans circumscripta (MOC) among 605 patients with para/tetraplegia. MOC proved significantly more common after total than after subtotal spinal cord injuries. MOC was not observed in any case above the motor level of the spinal cord lesion. This neurological relationship appears to "explain" the finding that MOC is more common in para/tetraplegia of traumatic origin (more complete spinal cord lesions) than among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

1985
1985
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
0
11
0
6
Order By: Relevance
“…In general, no association was found between NHO and race or gender, 13,19 although in some studies a slightly Figure 1 Visual approach to the pathophysiology of NHO in SCI patients. OAC: oral anti-coagulant.…”
Section: Risk Factorsmentioning
confidence: 97%
See 4 more Smart Citations
“…In general, no association was found between NHO and race or gender, 13,19 although in some studies a slightly Figure 1 Visual approach to the pathophysiology of NHO in SCI patients. OAC: oral anti-coagulant.…”
Section: Risk Factorsmentioning
confidence: 97%
“…Although Catz et al 37 did not ®nd a relationship between radiologically diagnosed NHO and the severity of the motor de®cits, other authors have reported that complete transverse SCI is more commonly associated with NHO than incomplete SCI with relative risks (RR) reported between 2.0 ± 4.2. 1,13,14,19,21,22,24,88 Also, NHO is less frequently reported (55%) in patients with lumbosacral or conus-cauda lesions, which regain or retain ambulation. 88 Other clinical factors associated with NHO are the presence of pressure sores, 6,21,22,24,30,47 urinary tract infections or renal stones, 3,4,6,24,100 deep venous thrombosis (DVT), 24 severe spasticity, 22 and (micro) trauma.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations